Long-Term Improvement in a Chinese Cohort of Glucocorticoid-Resistant Childhood-Onset Myasthenia Gravis Patients Treated With Tacrolimus - Bi, Zhuajin; Cao, Yayun; Lin, Jing; Zhang, Qing; Liu, Chenchen; Gui, Mengcui; Bu, Bitao (Frontiers in Neurology, 2022)
Objectives: To evaluate the long-term outcome of childhood-onset myasthenia gravis (CMG) with an inadequate response to glucocorticoids, and investigate factors associated with clinical improvement and favorable outcome following tacrolimus treatment. Methods: A retrospective analysis was conducted a cohort of CMG patients who had not improved satisfactorily after sufficient prednisone therapy for at least 8 weeks. All patients were given tacrolimus in doses of 2-3 mg for at least 6 months. The primary efficacy outcome was assessed using the prednisone dose, quantitative MG (QMG), and MG-activity of daily living (ADL) scores. The participants were divided into improved and unimproved groups based on changes in QMG scores to investigate the risk factors that affected tacrolimus efficacy. Results: In a cohort of consecutive 767 CMG patients, 206 cases (35.2 %) were resistant to corticotherapy. A total of 149 glucocorticoid resistant CMG patients were enrolled in this study. Generally, 113 cases out of the 149 patients (75.8％) responded well to tacrolimus (defined as minimal manifestation MM status or better). One month after initialing tacrolimus, there was a noticeable improvement in prednisone dose, QMG, and ADL scores, which continued to improve throughout the study. More importantly, the prednisone was eventually stopped in 89 of the patients (78.8%). Thymus type (odds ratio (OR)=3.156, 95% confidence interval (CI) 1.427 6.978; P = 0.005) and pre-intervention status (OR=0.284, 95％CI 0.109 0.741; P=0.010) were independent predictors of tacrolimus efficacy after controlling for confounding factors in multiple logistic regression. Conclusion: The majority of glucocorticoid-resistant CMG patients have a good long-term prognosis after adding tacrolimus. Thymus type and pre-intervention status can serve as potential predictors affecting the efficacy of tacrolimus.